New findings on fiber intake in children - Diana Sunardi (Indonesian Nutrition Association, 2022)
Fibre is an essential component of the human diet that is crucial for human health, the physiological and functional effects of dietary fibre are associated with a wide range of short-term and long-term health benefits. Fibre provides an energy source for the gut microbiome. The fermentation of fibre by the gut microbiome results in the production of a variety of compounds with short-term and long-term health benefits that extend beyond the gut, to the immune system and organs such as the liver, kidneys and even the brain. The short-term benefits include supporting the immune system, especially within the gut itself, preventing or ameliorating autoimmune diseases such as diabetes, inflammatory arthritis, inflammatory gastrointestinal disorders and allergic disease.